Strenghts of overseas Filipino workers' families (case studies) - Palac, Cleofe Cortez (Animo Repository, 2005)
This study is an in depth analysis of the dynamics of three strong and three non-strong families of Overseas Filipino Workers. It focuses on analyzing or assessing the strengths of these families. The aim is to compare the emerging strengths of the six families with those of the Family Strengths Inventory. This study made use of Case Study N - 1 replicated six times or six families. Qualitative approach was mainly used in the data gathering and data analysis. The methods used for data collection were interviews, observations and documentary analysis. There were two phases in the study. The first phase was the case analysis of each of the six families, which required in depth interviews, observation, pakikipagkuwentuhan with the family members. The profile of each family focused on the three aspects of family life and on their strengths. Themes were searched in each case towards identifying the strengths of each family. Results show that the six families have these strengths: resiliency through endurance, self sacrifice/suffering; open and constant communication; encouragement; family time and routine; priority for education; economic betterment; family closeness/ support from relatives; generosity/ sense of gratitude; strong prayer life/faith in God; respect; and a clear and consistent set of rules. Mutual support/shared responsibilities and goal focus emerged in the strong families but not in the non-strong families while hope and forgiveness surfaced in the non-strong families but not in the strong families. The six qualities of strong families as established in the Family Strengths Inventory (FSI) were also present in the six participants families: commitment; open and constant communication; spending time together; appreciation/affection; sense of spiritual well being and the ability to manage stress and crises. The following are family strengths, which appeared to be unique to the Filipino culture for they were not identified in the FSI and in foreign literature: forgiveness, economic betterment, priority for education and support given by in laws and relatives. The second phase of the study consisted of designing Strengths-Based Family Centered Enhancement Program for the OFWs families for the purpose of enhancing the identified strengths of the families.